The results of enroute monitoring of the laser gas pollutant pollutants in the atmosphere - Черногор, Леонид Феоктистович; Рашкевич, Александр Сергеевич (Eastern-European Journal of Enterprise Technologies, 2011)
We describe a laser monitor pollutant gases in the atmosphere. The method and the measurement results. It is proposed to use a laser display as a basic means for remote control zones emergencies